Soil salt balance in a cotton field under drip irrigation and subsurface pipe drainage systems. (24th November 2021) - Heng, Tong; Feng, Gary; Yang, Li‐Li; He, Xin‐Lin; Yang, Guang; Li, Fa‐Dong; Xu, Xuan; Feng, Yue
Abstract: Soil salinization is a vital factor limiting crop yield in dryland oasis cropland. A film‐mulched drip irrigation and subsurface pipe drainage (MDI‐SPD) system has been proved to be highly efficient at mitigating salination globally. However, the soil salt balance in time and spatial dimension is unclear in this system. A MDI‐SPD experiment was conducted for 4 yr (2015–2019) in a field in Manas River Basin, western China. The subsurface drainage pipes were installed at a depth of 1 m with a space of 15 m. Three long‐term observation points were set at 0, 5, and 7.5 m horizontal from the subsurface pipe and served as long‐term observation points in 0‐to‐20‐, 60‐to‐80‐, and 180‐to‐200‐cm soil layers. Results after 4 yr indicated that the total salt output in the irrigated area was 260 t, with 103 t of salt drained by the subsurface pipe (40% of the total salt output in the irrigation area), and the seed cotton yield increased by 52%. Soil salt balance indicated desalination. The electrical conductivity (EC) of subsurface pipe drainage was positively correlated with drainage flow and salt discharge and negatively correlated with drainage discharge and time ( P < .05). If salt leaching stops, soil EC at the 0‐to‐200‐cm depth could reach 15 dS m –1 in 8 yr. Thus, two or three uses of MDI‐SPD measures in the next 8 yr should suffice to maintain the soil salt at a low concentration. An increase in shaft drainage would also reduce the deep seepage of salt. Core Ideas: Results from a 4‐yr study showed that using drip irrigation with subsurface pipe systems improved cotton yield. Subsurface pipe systems drained 103 t salt, 40% of the total salt discharge over 4 yr. We quantified salt accumulation due to shallow groundwater recharge in the tillage layer. Subsurface pipe systems increased cotton yield by 52% in saline alkali land. Soil salt should be leached once every 3 yr without changing the leaching measures.